Analisis Implementasi Standar Akuntansi Keuangan Entitas Tanpa Akuntabilitas Publik Pada Koperasi Serba Usaha Pkk Di Handil - Andi Indrawati3, Adinda Ranandhea Robin Jonathan 2 (EKONOMIA, 2021)
This study aims to find out how the implementation of this Cooperative Financial Report is the Standard SAK ETAP Cooperative Bina Bersama (KSU) in collaboration with PKK. This study uses a quantitative descriptive analysis method, namely by collecting and describing data in the field, then classified, analyzed, and then interpreted so that it can provide a clear picture of the conditions under study to draw general generalization conclusions. This study aims to determine the implementation of SAK ETAP in Multipurpose Cooperatives (KSU) in collaboration with PKK. The benefit of this research is to assist Cooperatives in implementing Financial Accounting Standards for Entities Without Accountability. The results of this study conclude that the application of the financial statements of KSU Bina Bersama PKK is not fully in accordance with the Financial Accounting Standards for Entities Without Public Accountability (SAK ETAP). and the absence of cash flow reports and reports of changes in equity in the KSU Financial Development Collective PKK report.